Characterization of spinal microglial activation in a mouse model of imiquimod-induced psoriasis - Fumihiro Saika; Yohji Fukazawa; Shiroh Kishioka; Norikazu Kiguchi (Elsevier, 2023)
Although microglia are associated with chronic pain, the role of spinal microglia in the regulation of itch remains unclear. In this study, we characterized spinal microglial activation in a mouse model of imiquimod (IMQ)-induced psoriasis. Hypertrophic (activated) microglia were observed throughout the spinal cord after the topical application of IMQ. Furthermore, the mRNA expression of microglial markers and inflammatory mediators was upregulated. Ablation of itch-related sensory neurons using resiniferatoxin decreased itch-related scratching behavior and the number of hypertrophic microglia in the spinal dorsal horn. Conclusively, sensory neuron input may partially contribute to spinal microglial activation after IMQ application.